The Concept of State Defence on Spatial Planning Training and Education Of UPN “Veteran” of East Java - Winasih, S. S. Y.; M. Safeyah; H. Prasetyo (Nusantara Science and Technology Proceedings)
State-defense is an attitude and behavior that is imbued by a sense of love to the Republic of Indonesia which is based on Pancasila and the constitution of 1945. All citizens are entitled and must participate in an effort of defending the country. The fundamental consciousness to state-defense is the willingness to serve and to sacrifice in the defense-effort of the country. The concept of state-defense is interpreted physically by taking up arms against the enemy, while a non-physical interpretation of the concept may defined as any attempts to defend the state by raising nationalism, which is consciously living as a citizen of the nation and the state, imparting passion for the country and play an active role in advancing the nation. UPN “Veteran” of East Java, as the state-defence campus, carry out the principal of state-defense into the educational curriculum. The Area Arrangement for Integrated Trainings & Education of State-Defense in UPN “Veteran” of East Java is the implementation of that principle. These area arrangements are used as the facility of state-defense basic training and education for university students, lecturers and employees as well as the general public. The area arrangements proposal preceded by the location survey to identify the potential and the threat of the area, which is then followed by configuring the site-planning concepts and generating planning images for the training area.